Miscanthus sinensis 'Morning Light' Morning Light Maiden Grass: FPS407/FP407, 6/2007 - Gilman, Edward (EDIS, 2024)
This document provides an overview of Miscanthus sinensis ‘Morning Light’, commonly known as ‘Morning Light’ maiden grass. It describes the plant’s physical characteristics, including its height, spread, and fine-textured foliage. The document highlights its ornamental uses in landscapes, such as mass planting, borders, and as an accent. It also covers the plant’s adaptability to various soil types, its drought tolerance, and its preference for full sun. Additionally, the document mentions the plant’s invasive potential and provides information on its propagation and pest resistance. Original publication date September 1999.